Mengurai Wacana Sastra Hibrida: Sebuah Istilah Popularitas Sastra - Sarif Syamsu Rizal (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This article entitled “Mengurai Wacana Sastra Hibrida: Sebuah Istilah Popularitas Sastra” aims to present viewpoint for an interpretative of theoretical application to understandings of decomposing discourse on hybrid literature phenomenon. The discussion of this article is in the form of theoretical description, findings, and other researchs substance obtained from any references to be the bases of research activity to compile a clear opinion framework of problem statement, which is going to be tested. The theories are in the form of literary history from the old English to the modern English period, the findings are in the form of facts of hybridity and hybrid literature, also other research substances are in the form of summary of hybridity discourses in online media